A Solid Ultra Fine Self-Nanoemulsifying Drug Delivery System (S-SNEDDS) of Deferasirox for Improved Solubility: Optimization, Characterization, and In Vitro Cytotoxicity Studies - Alaa Alghananim; Yıldız Özalp; Burcu Mesut; Nedime Serakinci; Yıldız Özsoy; Sevgi Güngör (Pharmaceuticals, 2020)
The research work was designed to develop a solid self-nanoemulsifying drug delivery system (S-SNEDDS) of deferasirox (DFX). According to the solubility studies of DFX in different components, Peceol, Kolliphor EL, and Transcutol were selected as excipients. Pseudo-ternary phase diagrams were constructed, and then SNEDDS formation assessment studies and solubility of DFX in selected SNEDDSs formulations were performed. DFX loaded SNEDDS were prepared and characterized. The optimum DFX-SNEDDS formulations were developed. The relative safety of the optimized SNEDDS formulation was examined in a human immortalized myelogenous leukemia cell line, K562 cells, using the MTT cell viability test. Cytotoxicity studies revealed more cell viability (71.44%) of DFX loaded SNEDDS compared to pure DFX (3.99%) at 40 μM. The selected DFX-SNEDDS formulation was converted into S-SNEDDS by adsorbing into porous carriers, in order to study its dissolution behavior. The in vitro drug release studies indicated that DFX release (Q5%) from S-SNEDDS solidified with Neusilin UFL2 was significantly higher (93.6 ± 0.7% within 5 min) compared with the marketed product (81.65 ± 2.10%). The overall results indicated that the S-SNEDDS formulation of DFX could have the potential to enhance the solubility of DFX, which would in turn have the potential to improve its oral bioavailability as a safe novel delivery system.